Identification of in vitro metabolites of the novel anti-tumor thiosemicarbazone, DpC, using ultra-high performance liquid chromatography-quadrupole-time-of-flight mass spectrometry - Stariat, Ján; Kovaříková, Petra; Kučera, Radim; Klimeš, Jiří; Kalinowski, Danuta S; Richardson, Des R; Ketola, Raimo A (Analytical and bioanalytical chemistry, 2013)
Di-2-pyridylketone-4-cyclohexyl-4-methyl-3-thiosemicarbazone (DpC) is a promising analogue of the dipyridyl thiosemicarbazone class currently under development as a potential anti-cancer drug. In fact, this class of agents shows markedly greater anti-tumor activity and selectivity than the clinically investigated thiosemicarbazone, Triapine®. However, further development of DpC requires detailed data concerning its metabolism. Therefore, we focused on the identification of principal phase I and II metabolites of DpC in vitro. DpC was incubated with human liver microsomes/S9 fractions and the samples were analyzed using ultra-performance liquid chromatography (UPLC(TM)) with electrospray ionization quadrupole-time-of-flight (Q-TOF) mass spectrometry. An Acquity UPLC BEH C(18) column was implemented with 2 mM ammonium acetate and acetonitrile in gradient mode as the mobile phase. The chemical structures of metabolites were proposed based on the accurate mass measurement of the protonated molecules as well as their main product ions. Ten phase I and two phase II metabolites were detected and structurally described. The metabolism of DpC occurred via oxidation of the thiocarbonyl group, hydroxylation and N-demethylation, as well as the combination of these reactions. Conjugates of DpC and the metabolite, M10, with glucuronic acid were also observed as phase II metabolites. Neither sulfate nor glutathione conjugates were detected. This study provides the first information about the chemical structure of the principal metabolites of DpC, which supports the development of this promising anti-cancer drug and provides vital data for further pharmacokinetic and in vivo metabolism studies.
Keywords: Microsomes, Liver; Chromatography, High Pressure Liquid; tandemová hmotnostní spektrometrie; Tandem Mass Spectrometry; lidé; protinádorové látky; thiosemikarbazony; Humans; jaterní mikrozomy; Antineoplastic Agents; Thiosemicarbazones; vysokoúčinná kapalinová chromatografie